Juridical activism and regional integration : lessons from the European Court of Justice - Rozo, Carlos (1997)
Seeks to illustrate that judicial activism of the European Court of Justice has been a vital catalyst of the integration process. Opines that without it, the achievements of the European integration efforts would not have been as lasting or as deep as they have actually been.